Meningkatkan Hasil Belajar Siswa Pada Penjumlahan Dan Pengurangan Pecahan Dengan Menggunakan Strategi Pembelajaran Berbasis Masalah Di Kelas V Sd Negeri 200201 Padangsidimpuan - Hasibuan, Erwina Azizah (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2017)
This research is include a clasroom action research (PTK). This research is done in SDN 200201 Padangsidimpuan. Technique analyzing data is analysis data qualitative and quantitative. The result of this research show that the increasing of of the learning result of the students. Before the test is done from the pre-test the average of the pre-test score of the student is 20,2, after the action is done in cycle 1 from the result of the post-testthe average of the students score increaase become 58,7. Then after reviewing is done in cycle II, from the cycle II, the average of students result increase 76,3. The increasing of the students also can be seen from the finishing study of the students classically, the increasing from the pre-test is 0% become 68,6% in cycle I and increase become 91,4% in cycle II. In the first meeting of the first cycle the percentage of the teacher activities is 56% (enough) and in the second meeting in the firsy cycle the percentage of teacher activities is 65% (enough). After doing a reviewing in cycle Ii, teacher activity increase for the first meeting in the second cycle the persentage is 79% (good) and in second meeting in the second cycle the percentage is 88% (very good). While the percentage of the students activity in the first meeting in the first cycle is 42% (less) and in the second meeting in the first cycle is 50% (less). In the first meeting in the second cycle the percentage is 75% (good) and in the second meeting in the second cycle the percentage is 83% (good). Based on the result of the classroom aaction research that has done in 2 cycles can be conclude that the using of PBM strategies can increase the result of the learning of the student in counting and reducing numbers in class V SDN 200201 Padangsidimpuan T.A. 2016/2017.